Modelling the correlations between interest rate and other components of economic policy - Coralia Emilia POPA; Lorena TUPANGIU (Finanţe: Provocările viitorului, 2017)
Both the government and the monetary authorities have accepted that a strong nominal anchor is vital in establishing and implementing a sound monetary policy. The special importance of the interest rate in the proper functioning of the modern economy cannot be underestimated. The way it varies is relevant in establishing the level of economic well-being of each individual or business organization within the country. At the same time, the credibility of economic policy promoted by the government is very often measured by the level of the most representative interest rates. Therefore, it is important to analyze how the variation in interest rates influences the macroeconomic variables of the economy.